Probiotic characteristics of exopolysaccharides-producing Lactobacillus isolated from some traditional Malaysian fermented foods - Suliman, Eilaf Suliman Khalil; Abd Manap, Mohd Yazid; Mustafa, Shuhaimi; Amid, Mehrnoush; Aljoubori, Ahmed; Alhelli, Amaal Mohammed (Taylor & Francis, 2018)
This study aims to evaluate the probiotic properties of Lactobacillus strains producing exopolysaccharides (EPS) isolated from different Malaysian fermented foods. Thirty lactobacilli species were isolated, and six of these (TAP1, PIC7, BU11, BU14, TAP16, and TEMP9) were shown to exhibit probiotic characteristics with the potential to produce EPS. The isolates were evaluated for their tolerance to low pH, bile salts, antimicrobial potential, and cell surface properties. The strains were identified using API50CHL and 16S rRNA gene sequences as Lactobacillus belonged to the species fermentum and plantarum. The Lactobacillus strains exhibited high survivability tolerance to low pH and bile salts (above 90%). All strains exhibited auto-aggregation (33.63–59.63%), co-aggregation (24.37–41.9%), and hydrophobicity (16–65.77%) ability. The strains displayed no transferrable antibiotics and antagonistic activity against pathogenic bacteria. Therefore, it indicates that Lactobacillus strains could act as promising probiotic candidates.